PENGARUH PROMOSI, KUALITAS PRODUK DAN PERSEPSI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN DI SHOPEEPENGARUH PROMOSI, KUALITAS PRODUK DAN PERSEPSI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN DI SHOPEE - lim, ian (SCIENTIA JOURNAL, 2025)
The development of e-commerce in Indonesia has experienced rapid growth, especially in the cosmetics industry. Shopee as one of the leading e-commerce platforms plays an important role in influencing consumer purchasing behavior. One of the leading local cosmetic brands, Wardah, uses Shopee as a medium for distributing its products online. This study aims to analyze the influence of promotions, product quality, and consumer perceptions on purchasing decisions for Wardah products on the Shopee platform. This study uses a quantitative approach with a survey method by distributing questionnaires to 385 respondents who are active Shopee users and have purchased Wardah products in the last 12 months. The data collected was analyzed using multiple linear regression. The results showed that promotions, product quality, and consumer perceptions have a positive and significant effect on purchasing decisions. Product quality proved to be the dominant factor in driving purchasing decisions, followed by effective promotions and positive consumer perceptions. These findings indicate the importance of companies to maintain product quality consistency and strengthen promotional strategies that are in line with digital consumer expectations. Consumer perceptions have also been shown to play an important role in shaping trust and purchase intentions. The practical implication of this study is the need to optimize promotional features on Shopee such as live streaming, exclusive vouchers, and collaboration with influencers. In addition, supervision of product authenticity on digital platforms must be improved so that consumer perceptions remain positive. This study provides theoretical contributions to the development of consumer behavior literature in a digital context and can be used as a reference in formulating e-commerce-based marketing strategies. Keywords: Promotion, Product Quality, Consumer Perception, Purchase Decision, Shopee, Wardah.